Hippocampal Inactivation Disrupts the Acquisition and Contextual Encoding of Fear Extinction - Corcoran, Kevin A. (J Neurosci, 2005)
In recent studies, inactivation of the dorsal hippocampus before the retrieval of extinguished fear memories disrupted the context-dependent expression of these memories. In the present experiments, we examined the role of the dorsal hippocampus in the acquisition of extinction. After pairing an auditory conditional stimulus (CS) with an aversive footshock [unconditional stimulus (US)], rats received an extinction session in which the CS was presented without the US. In experiment 1, infusion of muscimol, a GABA(A) receptor agonist, into the dorsal hippocampus before the extinction training session decreased the rate of extinction. Moreover, when later tested for fear to the extinguished CS, all rats that had received hippocampal inactivation before extinction training demonstrated renewed fear regardless of the context in which testing took place. This suggests a role for the dorsal hippocampus in both acquiring the extinction memory and encoding the CS–context relationship that yields the context dependence of extinction. In experiment 2, inactivation of the dorsal hippocampus before testing also disrupted the context dependence of fear to the extinguished CS. In experiment 3, quantitative autoradiography revealed the boundaries of muscimol diffusion after infusion into the dorsal hippocampus. Together, these results reveal that the dorsal hippocampus is involved in the acquisition, contextual encoding, and context-dependent retrieval of fear extinction. Learning and remembering when and where aversive events occur is essential for adaptive emotional regulation.